SISTEM KADERISASI PARTAI KEBANGKITAN BANGSA (Studi Pada DPW PKB Jawa Tengah) - oktanila faria; susilo Utomo; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2016)
Political recruitmen function in today era reform is not implemented properly. Political party must recruits its candidates for legislative body using strict system regarding stages and requirements. It is important in order creates integrity public official.PKB Party is a political party who carry Islam Tradisional ideology and becames a political forum for NU (Nahdlatul Ulama). The majority of strategic officials is fulfill by cadres who have a family relationship with the famous local Kyai there. This reason can lead to indicated of patrimonial political practice.The purpose of this research is to knowing about how PKB Party in Central Java recruits and forming the cadres. The method used is a qualitative research model, with descriptive type. The primary data obtained through interviews with sources in this case the DPW board PKB Party in Central Java. Secondary data was obtained through literature and articles that are relevant to this research focus.Based on the finding, according to the party rules No. 02 of 2012 on The Forming of Cadres, PKB Party implements level cadres in three levels, namely KTP (Beginner Forming of Cadres), KTM (Intermediate Forming of Cadres), KTA (Above Forming of Cadres).The conclusion is that the forming of cadres implemented by DPW PKB party in Central Java in the period 2012-2017 are less democratic, it is happened because the party has not working agenda like in the AD/ART Party.Keyword : Political Recruitment, DPW PKB in Central Java,the Forming of Cadres